Impact of data security on users' trust and loyalty in digital platforms in Kuala Lumpur - Tai , Buo Ting (2024)
In today’s digital age, data protection is common because people have shared vast data across platforms, with over 120 zettabytes generated in 2023. While advancements in technology have simplified data collection and analysis, privacy, transparency, and security concerns persist, risking breaches and misuse. High profile incidents, like the misuse of Facebook data, erode user trust and loyalty, emphasising the need to explore how privacy and transparency practices influence user confidence in digital platforms. The research objective is to investigate how data security can impact user’s trust and loyalty based on digital platforms in Kuala Lumpur using the TAM and PCT model. Quantitative research using questionnaires was conducted on a sample size of 386 for empirical analysis. The results show that perceived ease of use and trust, as well as trust and loyalty, have significant relationships. However, perceived usefulness, data privacy concerns, and data transparency show no significant relationship with trust. Hence, this final year project has provided results and findings on the topic of data and digital platforms user’s trust and loyalty.